MOF-derived cobalt manganese phosphide as highly efficient electrocatalysts for hydrogen evolution reaction. (26th March 2022) - Duan, Donghong; Feng, Jiarong; Guo, Desheng; Gao, Jie; Liu, Shibin; Wang, Yunfang; Zhou, Xianxian
Abstract: Hydrogen is considered as a viable alternative to traditional fossil fuels. Hydrogen evolution reaction (HER) by electrochemical water splitting is the most reliable and effective way for the sustainable production of pure hydrogen. The design and synthesis of highly active and stable non-noble-metal-based electrocatalysts is the core of the large-scale application of this technology. Herein, peony petal-like CoMnP/NF nanomaterials growing on nickel foam (NF) are prepared via facile hydrothermal and phosphorization methods. The results showed that CoMnP/NF had excellent HER activity in acidic and alkaline media. In 0.5 M H2 SO4, CoMnP/NF only needed 66.6 mV overpotential to drive the current density of 10 mA cm −2, with a Tafel slope of 38.8 mV dec −1 . In addition, a particularly low overpotential of 53.9 mV and Tafel slope of 63 mV dec −1 are required to achieve the same current density in the 1 M KOH electrolyte. Meanwhile, the electrocatalyst showed good stability after 1000 cyclic voltammetry tests and 12 h I-T tests. In the 1 M KOH electrolyte, the current density of 10 mA cm −2 achieved with only 1.70 V battery voltage, and the electrocatalyst showed excellent stability. The performance of CoMnP/NF can be attributed to the synergistic effect between Co and Mn atoms and the high electrochemical surface area (ECSA). This study provides a valuable strategy for the synthesis of non-precious metals and high-performance catalytic materials. Highlights: Peony petal-like CoMnP/NF is prepared via facile two-step methods. CoMnP/NF electrocatalyst exhibit excellent catalytic activity and high stability. Mn doping could improve catalytic activity.